Primary cilia support cartilage regeneration after injury - Dike Tao; Lei Zhang; Yunpeng Ding; Na Tang; Xiaoqiao Xu; Gongchen Li; Pingping Niu; Rui Yue; Xiaogang Wang; Yidong Shen; Yao Sun (Nature Publishing Group, 2023)
Abstract In growing children, growth plate cartilage has limited self-repair ability upon fracture injury always leading to limb growth arrest. Interestingly, one type of fracture injuries within the growth plate achieve amazing self-healing, however, the mechanism is unclear. Using this type of fracture mouse model, we discovered the activation of Hedgehog (Hh) signaling in the injured growth plate, which could activate chondrocytes in growth plate and promote cartilage repair. Primary cilia are the central transduction mediator of Hh signaling. Notably, ciliary Hh-Smo-Gli signaling pathways were enriched in the growth plate during development. Moreover, chondrocytes in resting and proliferating zone were dynamically ciliated during growth plate repair. Furthermore, conditional deletion of the ciliary core gene Ift140 in cartilage disrupted cilia-mediated Hh signaling in growth plate. More importantly, activating ciliary Hh signaling by Smoothened agonist (SAG) significantly accelerated growth plate repair after injury. In sum, primary cilia mediate Hh signaling induced the activation of stem/progenitor chondrocytes and growth plate repair after fracture injury.